LEAD BIOACCUMULATION USING FISH SPECIMEN OF HOOGHLY RIVER DOWNSTREAM SEASONS - Soni, Sharmila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study was conducted to detect Pb metal content in sediment and muscle of fish (Mystus gulio Ham. – Buch.) of the of the river Hooghly, West Bengal, India. The study sites were selected at Batanagar (Bt), Budge Budge (Bg) and Birlapur (Br) sites. The samples viz. sediment and muscle of fish were collected and estimated by using atomic absorption spectrophotometer. The Pb content in sediments gradually significantly increasing trend towards downstream in the river Hooghly and winter season observed higher values in all the sites. But the content was found within the prescribed limit. The study sites observed significantly higher level of Pb accumulation in the muscle of the fish specimen (Mystus gulio) during summer compared to winter. The findings pose the risk of accumulation may be lower in fish muscle as per BSAF value. In future, this study may be beneficial to determine the water and sediment quality status in different stations of river Hooghly as well as other metals content in different fish species.